Analisis Kriminologis terhadap Relasi Kuasa Parsial dalam Kekerasan Seksual Inses oleh Ayah Kandung - Inezsafa Aura Maheswari Arifianto; Triny Srihadiati (Jurnal Ragam Pengabdian, 2026)
Incestuous sexual violence committed by biological fathers against their daughters represents one of the most severe forms of child victimization because it combines sexual abuse with the misuse of parental authority and emotional dependency. This study aims to analyze the forms of partial power relations employed by perpetrators during the victimization process from a feminist victimology perspective. A qualitative descriptive approach was employed through observations, in-depth interviews with victims, law enforcement officers, psychologists, and child protection practitioners, supported by document analysis. The findings indicate that perpetrators exploit their authority as fathers through psychological manipulation, emotional dependence, intimidation, threats, and trust abuse, creating unequal power relations that prevent victims from resisting or reporting the abuse. Victims experience multidimensional consequences, including severe psychological trauma, fear, social isolation, loss of self-confidence, and prolonged victimization reinforced by family silence and societal stigma. The study demonstrates that partial power relations are the primary mechanism sustaining incestuous sexual violence within families. Therefore, comprehensive victim-centered interventions involving legal protection, psychological rehabilitation, social support, and strengthened child protection policies are essential to prevent repeated victimization, facilitate recovery, and ensure justice for child victims while challenging patriarchal structures that normalize domination and silence.